Construction of new even-length type-II Z-complementary pair - Xiaoyu CHEN; Lianfeng SUN; Jiekun ZHANG; Yubo LI (Tongxin xuebao)
To enrich the parameter forms of Z-complementary pair (ZCP), the constructions of new Type-II ZCP were investigated.First, Type-II ( 2 k+2 N,( 2 k+2 −1)N )−<mtext>ZCP</mtext> was proposed by using iterative method.When N= 1, Z-optimal type-II ( 2 k+2 ,( 2 k+2 −1) )−<mtext>ZCP</mtext> could be obtained.Then, type-II ( 2 k+1 N+ 2 k+1 , 2 k+1 N+ 2 k+1 − N 2 )−<mtext>ZCP</mtext> was presented by combining the iterative method with the insertion method.When N= 2, Z-optimal type-II ( 3× 2 k+1 ,3× 2 k+1 −1 )−<mtext>ZCP</mtext> could be obtained.The proposed constructions can generate new even-length ZCP, and expand the number of existing ZCP.